TABLES OF INPUTS–OUTPUTS OF THE PELOPONNESIAN REGION CONCERNING THE YEARS 1995, 1998, 2000 - Vasilis, Panagou; Papaelias, Theodore (Journal of European Economy, 2017)
Input-output tables constitute a basic tool for the estimation of intra-sectoral relations among various fields (segments) of an economy, on the one hand, and for the calculation of Gross Domestic Product and Income, on the other. The problem of the regional income approach has become obvious since its first practical application. Economic development neither does it function harmonically nor counterbalancing. Therefore, after 1960 originated an attempt to estimate the regional input-output tables. So far no official data referring to the abovementioned tables have been presented. In this article, we estimate the tables for the years 1995, 1998 and 2000 in the Peloponnesian prefecture by means of methodology similar to that employed in the European Union